Peran Shalahuddin Al-Ayyubi dalam Perkembangan Islam di Mesir 1170-1193 M - rini, Syamsurini; Rahmat; Syakur, Nur Ahsan (Universitas Islam Negeri Alauddin Makassar, 2022)
Saladin al-Ayyubi was born in Tikrit in 1137 AD to a Kurdish Ayyubid family. Saladin in spreading Alhusunnah waljamaah in Egypt implemented efforts including; making Ahlusunnah Waljamaah the official sect, appointing Sunni qadis from the Ahlusunnah Waljamaah group, establishing several Sunni madrasas, changing the orientation of Al-Azhar University to Sunni, destroying books that teach Shia ideology, and taking physical action against Shia followers. As for the influence of Saladin al-Ayyubi in the spread of Ahlusunnah Waljamaah; succeeded in making progress in the political field by uniting Islamic regions, from Northern Egypt to Yemen, North Africa to Asia Minor. In the religious field, Saladin al-Ayyubi succeeded in erasing the traces of Shi'ism brought by the Fatimid dynasty in Egypt, and replacing it with the Sunni school of thought. In the field of education during Saladin's time, Islamic education experienced quite significant progress. In the social and cultural field, the progress achieved by Saladin in this field cannot be separated from the horrendous events that occurred at that time, namely the Crusades. Keywords: Shalahuddin Al-Ayyubi; Ahlusunnah Waljamaah; Mesir.